Accelerometry reveals nocturnal biphasic sleep behavior in wild giraffe - Burger-Schulz, Anna Lena; Thiel, Eric; Fennessy, Julian; Fennessy, Stephanie; Dierkes, Paul Wilhelm (Frontiers in Mammal Science, 2023)
Most research on mammalian resting and sleep behavior is conducted under controlled laboratory or zoo settings, with limited studies taking place in their natural habitats. To analyze these behaviors within a natural setting, actigraphy has been identified as a valuable method. This study sought to, firstly, measure inactivity and sleep in free-roaming Angolan giraffe (Giraffa giraffa angolensis) and, secondly, present their nocturnal behavioral rhythmicity. Three giraffe were fitted with an accelerometer-GPS device attached to an ossicone in November 2018 and behavioral data were collected daily between December 2018 and April 2019 to record their cranial movement. As giraffe show behavior specific head movements, sleep events could be detected as well as active and inactive behavior patterns. In this study, we analyzed how long giraffe were inactive during the night, how many sleep events they showed and for how long they were in the sleep position during the night. Giraffe were inactive for 490.8 ± 43.7 minutes during the night (from 19:00 to 7:00 local time), and a total of 857 sleep events were recorded with an average of 2.0 ± 1.0 events per night and total length of sleep per night averaged 8.6 ± 7.9. Further, results show a clear biphasic sleep profile during the night with peaks of inactivity and sleep events during the hours after sunset (21:00-23:00) and during the early morning hours before sunrise (3:00-5:00). We found individual differences for the number or sleep events, the total time sleeping as well as for inactivity. Interestingly, differences between months only were detected for inactivity. No differences were found for the number of sleep events nor for the total sleep time per night between months. For the first time, this study sheds light on the nocturnal sleep behavior and biphasic inactivity rhythm of giraffe in their natural habitat, providing additional support for previous findings indicating brief sleep episodes in giraffe.